Scoping the Vape Retail Environment and Retailers' Responses to Vape Control Measures in Selected Auckland Suburbs With Different Levels of Socio-Economic Deprivation - van der Sanden, Robin; Wilkins, Chris; Rychert, Marta; Ball, Jude; Hoek, Janet; Truman, Penelope; Kira, Geoff; Tautolo, El-Shadan (Pasifika Medical Association Group, 2026)
AIMS: Emerging research suggests exposure to vape stores and their proximity to schools play a role in vaping initiation among adolescents. In New Zealand, regulatory changes enacted that restrict sales of flavoured vape products to specialist vape retailers (SVRs) have led to growth in "store-within-a-store" (SWAS) SVRs in or beside convenience stores to circumvent restrictions. This paper assesses the number and type of SVR retailers, including SWAS, and their proximity to educational institutes (primary, secondary and tertiary) and marae across Auckland suburbs with different socio-economic deprivation levels. METHODS: Google Maps data and tools were used to assess SVR "type" and distance from schools, marae and other SVRs in selected Auckland suburbs. One hundred and sixty SVRs were examined across 14 suburbs. RESULTS: The median number of SVRs per suburb was 9.5. Forty-four percent of SVRs were SWAS. SWAS density increased with socio-economic deprivation, with high-deprivation suburbs containing a median of 8.5 SWAS compared with 2.0 in low-deprivation suburbs. Half of the SVRs (56%) were located within 300m of at least one educational institute. CONCLUSION: SWAS density in Auckland increased with neighbourhood socio-economic deprivation. SWAS retailers likely contribute to greater exposure to vape retail and products among adolescents in these areas.
Keywords: 32 Biomedical and Clinical Sciences; 4206 Public Health; 42 Health Sciences; Cancer; Prevention; Pediatric Research Initiative; 11 Medical and Health Sciences; General & Internal Medicine; 32 Biomedical and clinical sciences; 42 Health sciences; Adolescent; Vaping; Electronic Nicotine Delivery Systems; Socioeconomic Factors; Schools; New Zealand; Humans; Commerce; Adolescent; Vaping; Electronic Nicotine Delivery Systems; Socioeconomic Factors; Schools; New Zealand; Humans; Commerce; Adolescent; Vaping; Electronic Nicotine Delivery Systems; Socioeconomic Factors; Schools